2014
DOI: 10.1038/ismej.2013.240
|View full text |Cite
|
Sign up to set email alerts
|

The role of quorum sensing signalling in EPS production and the assembly of a sludge community into aerobic granules

Abstract: Quorum sensing (QS) signalling has been extensively studied in single species populations. However, the ecological role of QS in complex, multi-species communities, particularly in the context of community assembly, has neither been experimentally explored nor theoretically addressed. Here, we performed a long-term bioreactor ecology study to address the links between QS, organization and composition of complex microbial communities. The conversion of floccular biomass to highly structured granules was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
213
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(226 citation statements)
references
References 43 publications
10
213
3
Order By: Relevance
“…The broad AHL spectrum suggests that the root microbial community has the capacity to synthesize multiple signals. This observation also corresponds with the profile of AHLs identified in the floccular sludge community (Tan et al, 2014). In addition, our results are consistent with a previous report that AHL-producing bacteria often produce long-chain rather than short-chain AHLs (Wagner-Dobler et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
“…The broad AHL spectrum suggests that the root microbial community has the capacity to synthesize multiple signals. This observation also corresponds with the profile of AHLs identified in the floccular sludge community (Tan et al, 2014). In addition, our results are consistent with a previous report that AHL-producing bacteria often produce long-chain rather than short-chain AHLs (Wagner-Dobler et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
“…As EPSs had been shown to participate in biofilm formation3738 and cell adhesion39, we speculated that EPS synthesized by strain BD3749 might play critical roles in aggregate formation. This speculation was confirmed by the observation that cells cultivated in glucose medium failed to aggregate under the same conditions, indicating that the formation of aggregates was dependent on the EPS synthesized from sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that C4-HSL and AI-2 have positive effects on EPS production and promote the granulation of aerobic sludge (Ren et al, 2010;Tan et al, 2014;Xiong and Liu, 2010), while DSF inhibits the production of EPS and disperses bacterial aggregates (Deng et al, 2011;Tao et al, 2010). The specific roles of these signal molecules on anaerobic sludge granulation is still unknown.…”
Section: The Roles Of Different Qs Regulation In Granulation Of Anaermentioning
confidence: 98%
“…To date, the types of signal molecules found in water and wastewater treatment systems include N-acyl-homoserine lactones (AHLs) in Gram negative bacteria, autoinducer-2 (AI-2) in interspecies communication, and diffusible signal factor (DSF) in intra-and interspecies bacteria (Feng et al, 2014;Shrout and Nerenberg, 2012). There are many papers demonstrating the positive effects of AHLs or AI-2 in aerobic sludge granulation (Li and Zhu, 2014;Ren et al, 2013Ren et al, , 2010Tan et al, 2014;Liu, 2012, 2010;Zhang et al, 2011) and increasing the efficiency of the granulating process by improving granular properties. AHLs add-back studies by Tan et al (2014) explained the promotion by AHLs in extracellular polymeric substance (EPS) synthesis and microbial aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation